The role of CD4+ T cells in visceral leishmaniasis; new and emerging roles for NKG7 and TGFβ - Na, Jinrui; Engwerda, Christian (Frontiers in Cellular and Infection Microbiology, 2024)
Visceral leishmaniasis is a potentially devastating neglected tropical disease caused by the protozoan parasites Leishmania donovani and L. infantum (chagasi). These parasites reside in tissue macrophages and survive by deploying a number of mechanisms aimed at subverting the host immune response. CD4+ T cells play an important role in controlling Leishmania parasites by providing help in the form of pro-inflammatory cytokines to activate microbiocidal pathways in infected macrophages. However, because these cytokines can also cause tissue damage if over-produced, regulatory immune responses develop, and the balance between pro-inflammatory and regulatory CD4+ T cells responses determines the outcomes of infection. Past studies have identified important roles for pro-inflammatory cytokines such as IFNγ and TNF, as well as regulatory co-inhibitory receptors and the potent anti-inflammatory cytokine IL-10. More recently, other immunoregulatory molecules have been identified that play important roles in CD4+ T cell responses during VL. In this review, we will discuss recent findings about two of these molecules; the NK cell granule protein Nkg7 and the anti-inflammatory cytokine TGFβ, and describe how they impact CD4+ T cell functions and immune responses during visceral leishmaniasis.